Overview of the Quarter Life Crisis in Generation Z who are Entering Early Adulthood - Sadri, Lely Ameliah; Siswanti, Dian Novita; Jafar, Eka Sufartianinsih (Polteknik Ilmu Pemasyarakatan, 2024)
Generation Z who are entering adulthood are experiencing various demands of developmental tasks which make generation Z face a quarter life crisis. This research aims to reveal the overview of the quarter life crisis in generation Z who are entering early adulthood. This research uses a qualitative research method with a case study approach through semi-structured interviews with 5 respondents aged 20-28 years, and 4 significant others. The data analysis technique uses theory driven analysis techniques. The research results show that generation Z experiences indecisiveness in making decisions, despair, negative self-evaluation, being trapped in difficult situations, anxious, depressed, and worried about interpersonal relationships. This crisis arises due to lack of confidence in one's abilities, fear of taking risks, not having goal, ease of accessing information, mastery of technology, competition in getting a job, social demands, and poor friendships. The impacts felt by generation Z include feelings of shame, stress, overthinking, hopelessness, health problems, spending more time on social media, and being encouraged to develop and get to know themselves. It is hoped that this research can be a source of information for generation Z in understanding and overcoming the quarter life crisis. Keywords: Early adulthood, Generation Z, Quarter life crisis